Induction of interferon-β and interferon signaling by TRAIL and Smac mimetics via caspase-8 in breast cancer cells. - Victoria Granqvist; Christian Holmgren; Christer Larsson (PLoS ONE)
Breast cancer prognosis is frequently good but a substantial number of patients suffer from relapse. The death receptor ligand TRAIL can in combination with Smac mimetics induce apoptosis in some luminal-like ER-positive breast cancer cell lines, such as CAMA-1, but not in MCF-7 cells. Here we show that TRAIL and the Smac mimetic LCL161 induce non-canonical NF-κB and IFN signaling in ER-positive MCF-7 cells and in CAMA-1 breast cancer cells when apoptosis is blocked by caspase inhibition. Levels of p52 are increased and STAT1 gets phosphorylated. STAT1 phosphorylation is induced by TRAIL alone in MCF-7 cells and is independent of non-canonical NF-κB since downregulation of NIK has no effect. The phosphorylation of STAT1 is a rather late event, appearing after 24 hours of TRAIL stimulation. It is preceded by an increase in IFNB1 mRNA levels and can be blocked by siRNA targeting the type I IFN receptor IFNAR1 and by inhibition of Janus kinases by Ruxolitinib. Moreover, downregulation of caspase-8, but not inhibition of caspase activity, blocks TRAIL-mediated STAT1 phosphorylation and induction of IFN-related genes. The data suggest that TRAIL-induced IFNB1 expression in MCF-7 cells is dependent on a non-apoptotic role of caspase-8 and leads to autocrine interferon-β signaling.